An innovative approach to improving writing skills in higher education - Bernal Lloréns, Mercedes; Puigcerver Peñalver, Mª Carmen; Sánchez-Ballesta, Juan Pedro (Journal of Management and Business Education, 2023)
In this paper we introduce an innovation activity which consists of a writing competition in a Faculty of Economics and Business at a large university in Spain. This activity allows us to assess the deficiencies that higher education students have in writing reports and to encourage students and staff to be aware of the relevance of written communication for their personal lives and their professional careers. This experience showed us that those students that enrolled in the competition had good marks in a multiple-choice exam with questions about orthography, grammar, punctuation and vocabulary but they found more difficulties in composing their own texts. This suggests that despite the years employed in learning the Spanish language prior to embarking on their higher education courses, the students do not have enough skills to compose texts at the advanced level that corresponds to professionals in Social Sciences. One implication of these findings is that higher education teachers should highlight the relevance of writing properly to their students and develop activities in those fields in which composition is compulsory.